Prevalence of Anatomical Variations Concerning the Drainage of Paranasal Sinuses: A CT-based Retrospective Cross-Sectional Study from Eastern India - Nalamolu, V K Sundeep; Kumar Jha, Sandeep; Patel, Mouli Kirti; Basha, Shaik Ahammad; Kavarthapu, Srilatha (Journal of Neonatal Surgery, 2025)
Background: Anatomical variations of the paranasal sinuses (PNS) are highly variable among individuals and can significantly affect mucociliary drainage, predisposing patients to rhinosinusitis. Particularly when considering surgery for Functional Endoscopic Sinus Surgery (FESS), which attempts to restore normal sinus drainage, a thorough evaluation of these variances is essential. Despite their clinical importance, there is a lack of in-depth studies on these variations within the Indian population. Objective: To determine the prevalence of anatomical variations affecting PNS drainage using computed tomography (CT) among patients in Eastern India. Materials and Methods: A retrospective cross-sectional study was conducted on 100 patients aged 20–70 years who underwent CT evaluation for suspected sinusitis at a tertiary care center in Jharkhand, India, between July and December 2024. Anatomical variations in the osteomeatal complex (OMU) and sphenoethmoidal recess (SER) were assessed using a 128-slice Siemens CT scanner. Data was analyzed using RStudio (v2025.05.1+513). Chi-square test and prevalence ratios (PR) with 95% confidence intervals (CI) were used to explore associations with sex. Results: Of the 100 patients (mean age 42.9 ± 15.5 years), 51% were male and 49% female. The most common anatomical variations observed were agger nasi cells (98%), supra bullar cells (93%), Type I uncinate process attachment (88%), deviated nasal septum (78%), and enlarged ethmoid bulla (72%). A statistically significant sex difference was found only for frontal bullar cells, which were more prevalent in females (PR = 0.40, 95% CI: 0.20–0.84, p = 0.01). Other variations showed no significant sex-based differences. Conclusion and recommended: Anatomical variations of the PNS are highly prevalent and show considerable inter-individual variability. CT evaluation provides critical insights for individualized surgical planning. Routine preoperative imaging is recommended to minimize complications and improve surgical outcomes, particularly in FESS.